An evaluation of the relationship between corporate social investment and financial performance - Kobo, Kgabo Lynn (University of Limpopo, 2016)
The researcher using Quantitative process is aimed to appraise Corporate Social Investment (CSI) in relation to Corporate Financial Performance (CFP). This research addressed theoretical paradigms of CSI, leadership strategies applied to implement CSI and stakeholder theory is presented. The study area was Johannesburg Stock Exchange FTSE/JSE Responsible Investment Index. The top 35 recorded companies were chosen, and then from top 35, only 5 companies were used (25 observations). Data from 2011 to 2015 were obtained from audited integrated financial statements, websites, publications and annual reports. CSI indexes and financial presentation measures of companies were taken from the annual reports to be analysed using simple regression equation to examine the link between corporate social investments to company’s fiscal presentation. This study revealed a strong positive linkage among company’s social investment strategy implementation and share price, turnover, and return on equity. Companies that implemented social investment strategy noticed increase in profit because of factors such customer awareness, good firm reputation and competitive advantage.
Thesis (MBA.) -- Unversity of Limpopo, 2016
Keywords: Corporate social investment; Financial performance; Corporations - Finance; Business enterprises - Finance